Tabela de vida das culturas para o feijoeiro (Phaseolus vulgaris L.), com ênfase nas pragas e seus danos, em três plantios no período chuvoso - P Calil, Antônio Cezar; Chandler, Leland; Domingos Galvão, José; W Dias Casali, Vicente; B Nogueira, Sebastião (Revista Ceres, 2025)
To gain a better understanding of the relationships between the pests of beans and the time of plant growth and development, beans (Phaseolus vulgaris L., cv ‘Negrito 897') were planted on three different dates (Nov. 20 and Dec. 16, 1980, and Jan. 12, 1981) during the rainy season of the agricultural year 1980-81 at Viçosa, Minas Gerais. The plant-pest development sequence was followed by the crop life table method.